Prosthesis and Hybrid Strategy Consideration for Treating Two-level Cervical Disc Degeneration in Hybrid Surgery - Li Y.; Fogel G.R.; Liao Z.; Tyagi R.; Liu W. (My University, 2025)
Study Design.Biomechanical analysis using a validated nonlinear finite element (FE) model.Objective.The aim of this study was to combine the strategy of two-level hybrid surgery (HS) to explore how prostheses affect cervical biomechanics.Summary of Background Data.Few FE studies have explored differences in biomechanical behavior between combined and stand-alone structured prostheses with HS. No FE studies have considered whether the prosthesis type and hybrid strategy influence two-level HS.Methods.Three prostheses-Prodisc-C, PCM, and DCI-were analyzed in flexion and extension during HS at C4-C6. There were two HS constructs: anterior cervical discectomy and fusion (ACDF) conducted at the C4-C5 levels and anterior cervical disc replacement (ACDR) conducted at C5-C6 levels (ACDF/ACDR); ACDR/ACDF.Results.Flexion motion at adjacent levels was greater than that of intact spine. A maximum increase of 80% was observed with PCM in the ACDF/ACDR group. Extension motion at adjacent levels for both hybrid strategies with PCM, however, was similar to that of intact spine (<10% change), whereas it increased by 14% to 32% with DCI. The strain energy-storing capability with DCI tended to be similar to that of normal discs. Facet stress at the infra-adjacent level, however, significantly increased with DCI in both groups, whereas it increased with PCM and Prodisc-C only in the ACDR/ACDF group. All prostheses produced overloads on cartilage at the arthroplasty level. Prodisc-C and PCM cores showed stress above the yield stress of ultrahigh-molecular-weight polyethylene.Conclusion.Each prosthesis had advantages and disadvantages. In extension, DCI (vs. Prodisc-C and PCM) exhibited more compensation at adjacent levels in terms of motion, moments, and facet stress. The biomechanical performance of Prodisc-C was easily affected by the hybrid strategy. Thus, if only a combined-structure prosthesis is available for two-level HS (C4-C6 level), the hybrid strategy should be carefully evaluated and the ACDF/ACDR construct is recommended to avoid accelerating degeneration of adjacent segments.Level of Evidence. Copyright © 2018 Wolters Kluwer Health, Inc. All rights reserved.